The Power of Notary Grants as an Authentic Deal in the Settlement of Inherited Land Ownership Disputes - A. Sultan Sulfian; Firdaus Firdaus (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2022)
This study examines the power of a notarial grant deed as an authentic deed in the settlement of inherited land ownership disputes. This study aims to find out how the strength of a notary grant deed which has perfect evidentiary power is related to legal practices that occur in society where there are still many cases of cancellation of a notary grant deed by judges in court. This study is a normative legal research/doctrinal approach which is carried out by analyzing legislation or other legal materials related to the strength of a notary grant deed as an authentic deed in the settlement of inherited land ownership disputes. The results of this study illustrate that basically a notary grant deed has perfect evidentiary power which technically functions to provide guarantees of protection and legal certainty to grantors, grantees, heirs, and related parties. However, in reality the strength of proof of a notary grant deed in court is weak when there are deficiencies in its manufacture which cause the grant deed to be canceled by the judge. The weakness of the grant deed in the evidentiary process so far is because the data included in the deed is not comprehensive so that there are still legal loopholes that have the potential to cause disputes, both from the aspect of legal substance that has not been synchronized between various types of legislation, the role of the legal structure (Notary/PPAT) which has not been maximized in seeing the motivation and prerequisites of the applicant, and the legal culture factor of the community who does not yet have an adequate understanding of the legal mechanism for implementing grants.